From intervention to interventional system: towards greater theorization in population health intervention research - Linda Cambon; Philippe Terral; François Alla (BMC, 2019)
Abstract Background Population health intervention research raises major conceptual and methodological issues. These require us to clarify what an intervention is and how best to address it. This paper aims to clarify the concepts of intervention and context and to propose a way to consider their interactions in evaluation studies, especially by addressing the mechanisms and using the theory-driven evaluation methodology. Main text This article synthesizes the notions of intervention and context. It suggests that we consider an "interventional system", defined as a set of interrelated human and non-human contextual agents within spatial and temporal boundaries generating mechanistic configurations - mechanisms - which are prerequisites for change in health. The evaluation focal point is no longer the interventional ingredients taken separately from the context, but rather mechanisms that punctuate the process of change. It encourages a move towards theorization in evaluation designs, in order to analyze the interventional system more effectively. More particularly, it promotes theory-driven evaluation, either alone or combined with experimental designs. Conclusion Considering the intervention system, hybridizing paradigms in a process of theorization within evaluation designs, including different scientific disciplines, practitioners and intervention beneficiaries, may allow researchers a better understanding of what is being investigated and enable them to design the most appropriate methods and modalities for characterizing the interventional system. Evaluation methodologies should therefore be repositioned in relation to one another with regard to a new definition of "evidence", repositioning practitioners' expertise, qualitative paradigms and experimental questions in order to address the intervention system more profoundly.